THE EVALUATION OF CARBON IMPURITIES IN MOTOR OILS (Perner's Contacts, 2020)
The content of carbon impurities in the engine oil is one of the basic diagnostic variables, according to which it is decided whether it is necessary to change the engine oil. The paper presents the results of a comparison of the determination of the content of carbon impurities in motor oil by the REO-31 device according to the methodology used in the rolling stock warehouse in Česká Třebová and according to the methodology of the laboratory of tribotechnical diagnostics of the Faculty of Transport Engineering, University of Pardubice.
Keywords: degradation; engine oil; oil change; tribotechnical diagnostics; carbon impurities; soot